APLIKASI PEDULILINDUNGI MITIGASI BENCANA COVID-19 DI INDONESIA - Citra Eka Putri; Radja Erland Hamzah (Universitas Prof. Dr. Moestopo (Beragama), 2021)
In addition to adequate information about the potential for the Covid-19 disaster that has hit the world, especially Indonesia, mistakes in communicating information can cause uncertainty that worsens the situation. This study aims to analyze the disaster analysis model in the protected care application created by the government as a form of disaster mitigation in this country. This study uses a qualitative descriptive method. The object of the research is the disaster communication model in the Pedulilindung application launched by KOMINFO. The subjects of this research are parties involved in making the idea of a protected application, namely the head of the Public Relations Bureau of KOMINFO Mr. Ferdinandu Setu and also the users of the application. Methods of data collection using in-depth interviews and observations. as a result, KOMINFO conducts disaster response with a disaster communication model which includes, among others, information, communication, coordination, disaster mitigation and the media. media involvement ensures messages and information conveyed are accurate, fast and precise, targeting the use of social media in Indonesia to the fifth largest in the world, but the result is that many Indonesians are reluctant to use the application because it is not effective.